Atividade alelopática de Copaifera langsdorffii DESF: abordagem fitoquímica e molecular - Franco, Danilo Miralha [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The environmental conditions in the Cerrado, like drought and solar incidence, collaborate to diverse chemical laboratory that synthesizes and selects compounds produced by these plants. The seasonal contrast in the Cerrado vegetation types between dry and wet season is one of the factors that can alter the concentrations of secondary metabolites in plants. The compounds produced by secondary metabolism can be phenylpropanoids, terpenes, alkaloids and steroids that have biological activity and are responsible for the chemical interaction between plants. The allelochemicals are mediators of chemical communication between plants and mechanisms of action are related to numerous biochemical and physiological processes regulated by different sets of genes. Specific genes whose expression is controlled by microRNAs and other regulatory RNAs regulate several biological processes related to plant development. The use of molecular biology may elucidate the mechanisms of action responsible for phytotoxic physiological responses involved in allelopathic activity and show new targets in biochemical and physiological allelopathy. The evaluation of the allelopathic activity of enriched fractions of extracts and pure compounds with known allelopathic activity may elucidate mechanisms of action and effects at the molecular level associated with physiological pathways affected. The objective of this study was to evaluate the chemical profile and allelopathic potential of organic extracts of leaves collected Copaifera langsdorffii in dry and wet seasons. Therefore, we checked the germination speed index (GSI), root growth and the pattern of gene expression [SHORT- ROOT (SHR); miRNA166; FT HOMEODOMAIN LEUCINE ZIPPER (HD ZIP III) with genes REVOLUTA (REV), PHABULOSA (PHB) e PHAVOLUTA (PHV)] and phenotypic characteristics of seedlings of Sorghum bicolor. A comparison of phytochemical profile observed in the chromatograms indicates no qualitative changes in ...

As condições ambientais existentes no Cerrado, como déficit hídrico e incidência solar, colaboram para o diversificado laboratório químico que sintetiza e seleciona os compostos produzidos por essas plantas. O contraste sazonal nas fitofisionomias do Cerrado entre a época seca e úmida é um dos fatores que podem alterar as concentrações de metabólitos secundários em plantas. Os compostos produzidos pelo metabolismo secundário podem ser fenilpropanoides, terpenos, alcaloides e esteroides que possuem atividade biológica e são responsáveis pela interação química entre as plantas. Os aleloquímicos são mediadores da comunicação química entre os vegetais e os mecanismos de ação estão relacionados com inúmeros processos bioquímicos e fisiológicos regulados por diferentes conjuntos de genes. Diversos processos biológicos relacionados com o desenvolvimento vegetal são regulados por genes específicos cuja expressão é controlada por microRNAs e outros RNAs regulatórios. O uso da Biologia Molecular pode elucidar os mecanismos de ação fitotóxicos responsáveis pelas respostas fisiológicas envolvidas na atividade alelopática e mostrar novos alvos bioquímicos e fisiológicos na alelopatia. A avaliação da atividade alelopática de frações enriquecidas e substâncias puras de extratos com reconhecida atividade alelopática pode elucidar mecanismos de ação e os efeitos a nível molecular associados às vias fisiológicas afetadas. O objetivo do trabalho foi avaliar o perfil químico e o potencial alelopático de extratos orgânicos de folhas de Copaifera langsdorffii coletadas em épocas seca e úmida. Para tanto foram verificados o índice de velocidade de germinação (IVG), o crescimento radicular e o padrão de expressão gênica [SHORT- ROOT (SHR); miRNA166; FT HOMEODOMAIN LEUCINE ZIPPER (HD ZIP III) com os genes REVOLUTA (REV), PHABULOSA (PHB) e PHAVOLUTA (PHV)] e características fenotípicas de plântulas ...
Keywords: Fisiologia vegetal; Alelopatia; Biologia molecular; Expressão gênica; Copaíba; Acido ribonucleico; Plant physiology